The Baetodes complex (Ephemeroptera:Baetidae), phylogeny, biogeography, and new species of Mayobaetis - Nieto Peñalver, María Carolina (2015)
The Baetodes complex was erected by Lugo-Ortiz and McCafferty based on 2 characters: tarsal claws in the larva with a strong subapical seta and forceps in the male adult with basal segments with a distomedial projection. This complex includes the genera Baetodes, Lugoiops, Mayobaetis, Moribaetis, Prebaetodes, and Spiritiops. It is restricted to the New World, and larvae always live in well-oxygenated streams. A cladistic analysis was conducted for the complex on the basis of a matrix of 16 taxa and 92 morphological characters, all derived from external morphology of adults and larvae. A biogeographic analysis was carried out through Spatial Analysis of Vicariance to establish possible vicariant events that generated this taxonomic complex. The cladistic analysis under implied weights yielded 3 shortest trees, and the Baetodes complex was recovered as monophyletic. The biogeographic analysis reconstructed 3 disjunction nodes when no nodes were removed and 2 more when 1 node was removed. The vicariant events cannot be attributed unquestionably to any paleoclimatic or microtectonic event, but they coincide under certain scenarios. Mayobaetis yala, new species, from Argentina, was described. It can be distinguished from other species in the genus because segment I of the forceps lacks a projection in the male imago and the dorsal surface of the abdomen lacks a medial dark line in the larva.